Sleep/wake patterns and circadian typology in preschool children based on standardized parental self-reports. (April 2014) - Doi, Yuriko; Ishihara, Kaneyoshi; Uchiyama, Makoto
<x xml:space="preserve">Abstract</x> We studied the sleep/wake patterns and circadian typology of Japanese preschool children living in the Tokyo metropolitan area (193 boys and 190 girls, 4–6 years of age) from June to July 2012 based on a standardized parental self-reporting questionnaire. Our major findings are as follows: (1) sleep/wake timing was delayed, and the duration of nocturnal sleep (sleep period as well as time in bed) increased from that on scheduled days (weekdays) to that on free days (weekends) for all ages. (2) The duration of daily sleep (24 h), including daytime nap, was longer for 4-year-old children compared with that in 5- to 6-year-old children, but not significantly different between scheduled and free days within each age group. (3) The distribution of chronotypes was 36.3% for morning (M)-type, 48.8% for neither (N)-type and 11.2% for evening (E)-type, and this distribution was independent of sex or age. (4) Sleep/wake timing delays were observed from M-type and N-type to E-type during scheduled and free days. (5) The duration of nocturnal sleep decreased but increased for 24-h sleep time from M-type and N-type to E-type on scheduled days. (6) Sleep durations did not differ among chronotypes on free days. (7) Chronotypes were associated with parents' diurnal preferences, mealtimes and attendance at kindergartens or childcare centers but not with sex, age, season of birth, exposure to multimedia or exposure to morning sunlight in their bedrooms. When these results were compared with those for older children and adolescents, similar sleep/wake patterns and circadian typology were observed, although to a lesser degree, in children as young as 4–6 years of age. Napping may compensate, in part, for an accumulated weekday sleep deficit. The distribution of chronotypes was associated with differences in sleep/wake timing and duration and was influenced by the parents' diurnal preferences and lifestyles. Further research on preschool children is required to investigate whether circadian typology affects their behavioral, emotional and cognitive development.